2015
DOI: 10.1002/j.0022-0337.2015.79.3.tb05888.x
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Time Compared to Clinical Procedures in Amalgam and Composite Posterior Restorations in U.S. Dental Schools: A Preliminary Study

Abstract: Dental clinicians have an expanding range of biomaterial choices for restoring tooth structure. Scientiic developments in cariology, advances in dental biomaterials, and patients' esthetic concerns have led to a reduction in amalgam restorations and an increase in composite restorations. The aim of this study was to compare teaching time with students' clinical procedures in amalgam and composite posterior restorations in dental schools across the United States. Academic deans in 60 schools were invited to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
0
20
0
2
Order By: Relevance
“… 11 A recent study showed that 47% of restorations placed by undergraduates in USA were amalgam. 12 Moreover, 75% of direct restorations placed in molar teeth by general dental practitioners in England and Wales are amalgam. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 A recent study showed that 47% of restorations placed by undergraduates in USA were amalgam. 12 Moreover, 75% of direct restorations placed in molar teeth by general dental practitioners in England and Wales are amalgam. 19 …”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Amalgam is no longer the first choice among instructors, students, or patients. 12 Time spent to teach amalgam will continue to fall, and perhaps it will be on preclinical basis, or cease to exist in the next decade. 7 Even in a post-amalgam era, dentists would still need to adhere to national and international guidelines of mercury hygiene 13 while removing old amalgam fillings or preparing existing restorations to act as the foundation restorations for crowns and fixed partial dentures.…”
mentioning
confidence: 99%
“…A series of studies from 2004 to 2007 from Lynch, McConnell and Wilson identified that curricula of dental schools in the United Kingdom, Ireland and North America were not incorporating modern techniques and therefore a certain “incompetence” existed with graduating dentists inappropriately restoring posterior teeth. Rey et al similarly described the need for an alignment of curricula reflecting the ever‐changing evidence base relating to direct restorative materials.…”
Section: Resultsmentioning
confidence: 99%
“…The students' attitude towards amalgam restorations and the di culty to convince the patients to undergo treatment with amalgam have been documented. 35,36 This factor may have resulted in a lower level of satisfaction among the level 10 students (p>0.05) ( Table 5). There was no statistical difference in the gender group (p>0.05) ( Table 5).…”
Section: Discussionmentioning
confidence: 99%